Coisa julgada relativa à decisão da questão prejudicial: regime jurídico, limites e proposições para o enfrentamento da litigiosidade pulverizada - Cavalcanti, Marcos de Araújo (2018)
The purpose of this thesis is to present a study of the issue preclusion in Brazil, in view of the changes made by arts. 503, §§1° and 2°, and 506 of the Brazilian Civil Procedure Code/2015. The work is structurally divided into four parts. The first one, subdivided into two chapters, establishes the methodological and conceptual premises that have repercussions in the course of the whole study, defining how issues should be decided in the context of the Brazilian Constitutional State, as well as the concept of a prejudicial question and the procedural consequences that it entails as it arises in the ongoing judicial proceedings. The second part, consisting of only one chapter, takes a comparative law approach to the procedure of the res judicata in the experience of American law. The third part, composed of two chapters, aims to define the res judicata effects in Brazilian law, identifying the issues raised by the claim and issue preclusion. Finally, the fourth part of the thesis, consisting of only one chapter, defines who can be bound by the effects of the issue preclusion, included the strangers. In the latter part, it is defined the types of litigation that the issue preclusion effects may prove adequate to prevent or avoid the problems arising from the isolated discussion of common questions. In summary, the present thesis seeks to present methodological and interpretative guidelines to overcome the difficulties that will arise with the application of the new legal regime of res judicata in Brazil